2020
DOI: 10.1186/s12943-020-01233-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the interplay between m6A modification and noncoding RNAs in cancer

Abstract: N6-methyladenosine (m 6 A) is one of the most common RNA modifications in eukaryotes, mainly in messenger RNA (mRNA). Increasing evidence shows that m 6 A methylation modification acts an essential role in various physiological and pathological bioprocesses. Noncoding RNAs (ncRNAs), including miRNAs, lncRNAs and circRNAs, are known to participate in regulating cell differentiation, angiogenesis, immune response, inflammatory response and carcinogenesis. m 6 A regulators, such as METTL3, ALKBH5 and IGF2BP1 have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
162
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 120 publications
(163 reference statements)
2
162
0
Order By: Relevance
“…Recent studies have discovered a number of lncRNAs modified by N(6)-methyladenosine in multiple cancers, and they can regulate gene expression and function through a series of complex mechanisms [ 37 42 ]. In turn, lncRNAs can target or modulate N(6)-methyladenosine regulators to influence the development of cancer [ 43 ]. However, the role of lncRNAs in the N(6)-methyladenosine modification of rRNA remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have discovered a number of lncRNAs modified by N(6)-methyladenosine in multiple cancers, and they can regulate gene expression and function through a series of complex mechanisms [ 37 42 ]. In turn, lncRNAs can target or modulate N(6)-methyladenosine regulators to influence the development of cancer [ 43 ]. However, the role of lncRNAs in the N(6)-methyladenosine modification of rRNA remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5) stimulate the demethylation process and are included under “eraser” complex ( 15 , 16 ). Extensive studies on m6A modification indicated toward its contribution in regulation of mRNA ( 17 ), long non-coding RNA (lncRNA) ( 18 ), microRNA ( 19 ), and circular RNA (circRNA) ( 20 ). m6A modification being an important RNA regulatory mechanism has been proved to play a critical role in regulating RNA processing, transportation, translation, and decay.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we also found that ALKBH5 could increase NANOG expression in glioma. Moreover, the m6A modi cation may be addressed by noncoding RNA [21]. Apart from the direct interaction of miR-1252-5p and 3'UTR of NANOG, we also found that miR-1252-5p could bind with 3'UTR of ALKBH5.…”
Section: Discussionmentioning
confidence: 69%
“…NANOG contributes to tumor cell growth and TMZ resistance in glioma [19,20]. N6-methyladenosine (m6A) is a common mRNA modi cation, and it is involved in the regulation of noncoding RNAs on tumorigenesis [21].AlkB homolog H5 (ALKBH5) is a representative m6A demethylase which can lead to the demethylation of mRNA in human disease [22]. ALKBH5 maintains tumorigenicity of glioma stem-like cells [23].…”
Section: Introductionmentioning
confidence: 99%